PERSPECTIVES OF COOPERATION BETWEEN BARTIN UNIVERSITY TURKEY AND PEOPLES FRIENDSHIP UNIVERSITY OF RUSSIA - Makarova, E.P.; Allahverdi, S.R.; Tumayan, A.F. (Bartın Üniversitesi, 2012)
[Abstract Not Available]